What are the expectations and experiences of a GMH research programme delivered in Bosnia-Herzegovina, Colombia and Uganda? A prospective longitudinal qualitative study - Stefan Priebe; Vian Rajabzadeh; Victoria Jane Bird; Francois van Loggerenberg; Michael McGrath (BMJ Open)
Objectives Global health research collaborations between partners in high-income countries and low-income and middle-income countries (LMICs) aim to generate new evidence, strengthen research capacity, tackle health inequalities and improve outcomes. Previous evaluations of such programmes have identified areas for improvement but consisted only of retrospective experiences. We conducted the first prospective study to assess the initial expectations as well as the final experiences of participants of a global health research programme.Design, settings and participants This study adopted a prospective longitudinal qualitative study, 38 participants of a global mental health research programme with partners in Bosnia-Herzegovina, Colombia, Uganda and the (UK). The interviewees included senior investigators, coordinators and researchers. Framework analysis was used to analyse the data.Outcome measures Participants were interviewed about their initial expectations at the inception of the research programme and their final experiences at the end.Results Many of the original expectations were later reported as met or even exceeded. They included experiences of communication, relationships, developed research expertise, further research opportunities and extending networks. However, other expectations were not met or only partially met, mainly on developing local leadership, strengthening institutional research capacity and opportunities for innovation and for mutual learning. Around equity of partnership and ownership of research the views of participants in the UK tended to be more critical than those of partners in LMICs.Conclusions The findings suggest that global health research programmes can achieve several of their aims, and that partners in LMICs feel equity has been established in the partnership despite the imbalance of the funding arrangement. Aims of global health research projects should have a realistic focus and be proportionate to the parameters of the funding arrangement. More resources and longer time scales may be required to address sustainable structural capacity and long-standing local leadership sufficiently.